Data Visualization and Prediction Model Analysis - Hua Ziyi (ITM Web of Conferences)
Data visualization plays an important role in the process of data analysis. It can transform complex data into intuitive charts, which helps us understand data more effectively. The purpose of this paper is to study the application of data visualization and compare different prediction models. In this work, I present three different prediction models and apply them on the US airline industry datasets by using Python as the programming language. Then these data sets are made into a bar graph and analy1zed through these three prediction models. Finally, this paper provides some suggestions on how to choose appropriate visualization tools based on data characteristics. This study not only enriches the application examples of data visualization, but also provides valuable reference for decision-making and predicting in data analysis.